Jesus feminist : an invitation to revist the Bible's view of women - Bessey, Sarah (New York : Howard Books, A Division of Simon & Schuster, Inc., 2013)
Gender roles have been debated for centuries, and now Sarah Bessey offers a clarion freedom call for all who want to realize their giftedness and potential in the kingdom of God. Through a thoughtful review of biblical teaching and church practices, Bessey shares how following Jesus made a feminist out of her.
Let us be women who love -- Introduction: A bonfire on the shore -- Jesus made a feminist out of me -- A redemptive movement -- Tangled-up roots -- The silent (?) women of Paul -- Dancing warriors -- Patron saints, spiritual midwives, and "biblical" womanhood -- A narrative reborn -- Reclaiming the church ladies -- Moving mountains one stone at a time -- Kingdom come -- Intimate insurgency -- The commissioning.
"Exploring God's radical notion that women are people, too."
Includes bibliographical references (pages 217-234).
Keywords: Women in Christianity; Sex role -- Religious aspects -- Christianity; Feminist theology